Respuesta :

Answer:

The vertex form of the equation is [tex]y = -\frac{1}{3}( x-1)^{2} +1[/tex].

Step-by-step explanation:

You will use the equation [tex]y=a(x-h)^{2} +k[/tex] to solve this parabola. (h, k) is the vertex. So, we plug this into the equation to get [tex]y= a(x - 1)^{2} +1[/tex].

Then, we substitute the point as our x and y to get [tex]-2 = 9a+1[/tex] (a lot of simplifying was done here). Then, add 2 to the right side of the equation and isolate the [tex]9a[/tex] to get [tex]9a = 3[/tex]. Finally, divide by 9 on both sides to get [tex]a=\frac{1}{3}[/tex].

Now, substitute your [tex]a[/tex] back into the equation to get y = [tex]-\frac{1}{3}(x-1)^{2}+1[/tex].

This is in vertex form. If the answer is needed in standard form, simply distribute and simplify to get [tex]y = -\frac{1}{3} x^{2} +\frac{2}{3} x+\frac{2}{3}[/tex].

ACCESS MORE